The spread of serophobia within brazilian political discourse - Filho, Evandro Alves Barbosa; Vieira, Ana Cristina de Souza (Seven Editora, 2023)
The article analyses the spread of serophobia within Brazilian political discourse. The research is qualitative and used discursive formulas for the treatment of the corpus. The analysis is based on works by Wendy Brown and Melinda Cooper. Serophobia, understood as the set of irrational and discriminatory practices and beliefs against HIV-positive individuals and groups vulnerable to HIV and AIDS, has been identified as a central element within the discourse of the Brazilian extreme right, who are committed to dismantling the National HIV/AIDS programme and advancing an agenda for affirming morality and traditional gender hierarchies. The scenario is one of attacking sexual and reproductive rights and universal access to HIV/AIDS treatment. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-095